PROBLEMS OF THE IMPLEMENTATION OF THE 2013 CURRICULUM IN ISLAMIC RELIGIOUS EDUCATION LESSONS IN FORMING AKHLAKUL KARIMAH AT SMK RAUDLATUL ULUUM-1 AEK NABARA LABUHANBATU - Saiful Akhyar Lubis; Wahyudin Nur Nasution; Tri Rifai Alam; M. Fajri Syahroni Siregar (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
The purpose of this study is the implementation of the 2013 curriculum in Islamic religious education subjects in shaping morality at SMK Raudlatul Uluum-1 Aek Nabara Labuhanbatu. Then what are the problems faced in implementing the 2013 curriculum in Islamic religious education subjects in shaping morality at SMK Raudlatul Uluum-1 Aek Nabara Labuhanbatu. Then find out the efforts that can be made to overcome the problems of implementing the 2013 curriculum in Islamic religious education subjects in forming morality at SMK Raudlatul Uluum-1 Aek Nabara Labuhanbatu. The research that the researcher carried out included qualitative research and when collecting the data used the Field Research method (Field Research). This data will be presented in descriptive form in the form of sentences. The data in this study will be collected and analyzed and then looked for validity.